Development of a multiplex real-time pcr assay for detection of fungal pathogens in invasive mycoses - Ismadi, Yasmin Khairani Muhammad (2024)
Invasive mycoses pose significant challenges to immunocompromised individuals, often resulting in severe morbidity and mortality. Current diagnostic methods are hindered by delays in identification and initiation of appropriate antifungal therapy, stemming from the limitations of conventional techniques. This study undertakes a thorough investigation into fungal DNA extraction protocols and the development of a multiplex real-time PCR assay for rapid identification of invasive fungal pathogens. This research aims to compare fungal DNA extraction methods and develop a multiplex real-time PCR assay capable of simultaneously identifying multiple fungal species commonly associated with invasive mycoses. Species-specific primer design and assay optimization target Aspergillus fumigatus, Aspergillus terreus, Candida albicans, and Candida glabrata. Results reveal certain extraction methods exhibiting superior sensitivity and time efficiency, with implications for clinical use. The developed multiplex real-time PCR assay demonstrates promising accuracy in identifying fungal pathogens. Analytical specificity testing, which involved detecting 65 isolates including various fungal strains alongside other reference strains, yielded a 100% identification rate for target organisms. Performance evaluation of the multiplex PCR assay using spiked blood samples showed high specificity and sensitivity, both at 100%, with positive predictive value (PPV) and negative predictive value (NPV) also at 100%. Overall, this research contributes to advancing laboratory diagnosis and management of invasive fungal infections. By addressing challenges in fungal DNA extraction and creating a high-performance multiplex PCR assay, this study lays the groundwork for more efficient and reliable diagnostic approaches, thereby enhancing patient care and treatment outcomes. Further validation studies on real clinical samples are recommended to confirm the applicability of these methodologies in the current clinical settings.